ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA WARUNG-WARUNG PECEL DI BLITAR - FITRIA IKA AGUSTINA (Universitas Teknologi Mataram, 2018)
Food business in Blitar develop from day to day in number, and this make the management of food business work harder to stay survival in the competition of the food business. This research is aimed at analyzing the effect of product quality, service quality, price, and location either partially or simultaneously on buying decision in pecel stall in Blitar. This research is associative study with quantitative approach. The sample were 100 respondents selected through purposive sampling. The data were collected through questionnaires. The collected data were analyzed with multiple linear regression. The research showed that product quality, service quality, price, and location have effect either partially or simultaneously on buying decision in pecel stall in Blitar and product quality is most dominant variable to affect the buying decision in pecel stall in Blitar. The management of the stall are suggested that they improve the product quality to make the buyer buying decision.Keyword : product quality, service quality, price, location, buying decision